MODERNISME BARAT DAN DAMPAKNYA PADA MASYARAKAT GLOBAL - Dasman Dasman (Komunitas Dosen Dakwah Institut Agama Islam Negeri (IAIN) Palu, 2012)
The study used two paradigm to understand and respond to changes leading to modernism especiallu in the West. The first is historical paradigm, while the second is socio-cultural paradigms. Based on these, western modernism has tremedous impacts on different spheres of life. The example includes such attitudes as establishment, arrogance, and materialism. Modernism involves capitalism in the process of industrial development and results in urbanization and mass mobilization to the cities. Modernism in the West is also able to change the social order and Islamic values that has been built up in world civilization in the East and West.